Piscirickettsia salmonis Imbalances the Innate Immune Response to Succeed in a Productive Infection in a Salmonid Cell Line Model. - Claudio A Álvarez; Fernando A Gomez; Luis Mercado; Ramón Ramírez; Sergio H Marshall (PLoS ONE, 2016)
Piscirickettsia salmonis is a facultative intracellular bacterium that causes the disease called "salmon rickettsial syndrome". Attempts to control this disease have been unsuccessful, because existing vaccines have not achieved the expected effectiveness and the antibiotics used fail to completely eradicate the pathogen. This is in part the product of lack of scientific information that still lacks on the mechanisms used by this bacterium to overcome infected-cell responses and survive to induce a productive infection in macrophages. For that, this work was focused in determining if P. salmonis is able to modify the expression and the imbalance of IL-12 and IL-10 using an in vitro model. Additionally, we also evaluated the role the antimicrobial peptide hepcidin had in the control of this pathogen in infected cells. Therefore, the expression of IL-10 and IL-12 was evaluated at earlier stages of infection in the RTS11 cell line derived from Oncorhynchus mykiss macrophages. Simultaneously, the hepcidin expression and location was analyzed in the macrophages infected with the pathogen. Our results suggest that IL-10 is clearly induced at early stages of infection with values peaking at 36 hours post infection. Furthermore, infective P. salmonis downregulates the expression of antimicrobial peptide hepcidin and vesicles containing this peptide were unable to merge with the infective bacteria. Our results suggest that P. salmonis is able to manipulate the behavior of host cytokines and likely might constitute a virulence mechanism that promotes intracellular bacterial replication in leukocytes cells lines of trout and salmon. This mechanism involves the generation of an optimum environment for the microorganism and the downregulation of antimicrobial effectors like hepcidin.